Description of the Characteristics of Patients Who Experience Hallucinations in the Nyiur Room and Reminiscence Room at the Regional Special Hospital of South Sulawesi Province - Harun, Basmalah (Hasanuddin Medan, 2022)
This study aims to determine the characteristics of patients who experience hallucinations in the Nyiur room and Kenanga room at the Regional Special Hospital of South Sulawesi Province. This research uses a quantitative research design with a survey approach. The total sample was 98 respondents. Sample selection was carried out using Total Sampling. The data collected is secondary data obtained from medical records, using descriptive statistical tests and analyzed using univariate analysis. The results of the analysis showed that the patients who experienced hallucinations in the palm room and ylang ylang room were based on age group, the most common being the 30–57-year-old group, 57 (58.2%), while based on gender, the most common were men, 51 (51). 52.0%), while based on occupation the most numerous were unemployed as many as 51 (52.0%), based on education the most numerous were elementary school level education as many as 37 (37.8%), and based on economics the most numerous were Those with low economic conditions were 68 (69.4%). It can be concluded that patients who experience hallucinations in the palm room and ylang ylang room are mostly > 30 years old, male, do not work, have an elementary school level education, and have a low economic background. For further research, more respondents and better measuring tools are needed to increase accuracy in order to provide more accurate information about the characteristics of hallucination sufferers.